The role of autophagy in the Arabidopsis self-incompatible pollen rejection response - Stuart R. Macgregor; Daphne R. Goring (Autophagy Reports, 2022)
In plants, macroautophagy/autophagy is an essential mechanism responsible for a large variety of processes throughout the plant’s lifecycle, including nutrient processing, immunity, stress responses and senescence. Previous studies had observed the presence of autophagosomes in an Arabidopsis sexual reproduction system that prevents self-fertilization (self-incompatibility), but their requirement in this pathway was unclear. Using autophagy-deficient mutants, we have recently found that autophagy is a key contributor in the Arabidopsis self-incompatibility response to reject self-pollen.